Development of Fluorescence Polarization Immunoassay for Imidacloprid in Environmental and Agricultural Samples - Zhou, Liangliang; Yang, Jiachuan; Tao, Zhexuan; Eremin, Sergei A.; Hua, Xiude; Wang, Minghua (Frontiers in Chemistry, 2020)
A fluorescence polarization immunoassay (FPIA) for the determination of imidacloprid (IMI) was developed with advantages of simple operation and short assays time. The haptens of IMI, acetamiprid (ACE) and thiamethoxam (THI) were conjugated with fluorescein isothiocyanate ethylenediamine (EDF) and 4’-Aminomethyl fluorescein (AMF) respectively to prepare six fluorescence tracers. The conjugation of IMI hapten and EDF (IMI-EDF) was selected to develop the FPIA due to the largest fluorescent polarization value increase in the presence of anti-IMI monoclonal antibody. Under the optimum condition, the limit of detection, 50% inhibition concentration and detection range of the FPIA were 1.7, 4.8 and 1.7-16.3 µg/L, respectively. The cross-reactivities (CRs) with the analogues of IMI were negligible except for imidaclothiz with CR of 79.13%. The average recovery of spiked paddy water, corn and cucumber samples were 82.4%-118.5% with the RSDs of 7.0%-15.9%, which indicated the FPIA had good accuracy. Thus, the developed FPIA was a potential tool for the rapid and accurate determination of IMI in agricultural and environmental samples.